Education Ethics Business for Increase Awareness of Environmental Living - Nurhalimah Sibuea (Universitas Muhammadiyah Enrekang, 2024)
One of the most set important social challenges for business is a balance between economics interests and maintain orders materialized ecologically sustainable development. Morals and ethics have a function to give the orientation of how and where we are heading in life, but the difference is that morality is a direct show of ways to go, while directing the choice of ethics precisely why you should move in such away? Business ethics is the application of ethical thinking in general, in business behavior. Business ethics is note a specific part of ethics which is different from ethics in general and are applicable only for business. If dishonesty is considered unethical and immoral, then anyone in business who are note honest with shareholders, employees, consumers or competitors, have acted in an unethical and immoral manner. According to the conventional ideology of economic development and preservation is a dichotomy that separated from one another. When in fact, both have a very close relationship and jointly become a national agenda that must be considered by the government and society in a country. This means that without an adequate environmental protection, development will be lost meaning (undermined). Thus, the nature of the sustainable development, is the balance between economic interests with ecological sustainability (ecology are: Science of learning about how living creatures interact with one another within an ecosystem). Economics learning goals leads students to have the abilities to resolve the various problems it faces. Therefore, through the educational values in business ethics expected of students have the knowledge and the provisions to be applied in everyday life which would note intentionally or engage in business activities